The Colonel and the King : Tom Parker, Elvis Presley, and the partnership that rocked the world - Guralnick, Peter (Little, Brown and Company, 2025)
"In early 1955, Colonel Tom Parker--manager of the number-one country music star of the day--heard that an unknown teenager from Memphis had just drawn a crowd of more than eight hundred people to a Texas schoolhouse, and headed south to investigate. Within days, Parker was sending out telegrams and letters to promoters and booking agents: "We have a new boy that is absolutely going to be one of the biggest things in the business in a very short time. His name is ELVIS PRESLEY." Later that year, after signing with RCA, the young man sent a telegram of his own: "Dear Colonel, Words can never tell you how my folks and I appreciate what you did for me.... I love you like a father." The close personal bond between Elvis and the Colonel has never been fully portrayed before. It was a relationship founded on mutual admiration and support. From the outset, the Colonel defended Elvis fiercely and indefatigably against RCA executives, Elvis's own booking agents, and movie moguls. But in their final years together, the story grew darker, as the Colonel found himself unable to protect Elvis from himself or control growing problems of his own. Featuring troves of previously unpublished correspondence, revelatory for both its insights and emotional depth, The Colonel and the King provides a unique perspective on not one but two American originals. A tale of the birth of the modern-day superstar (an invention almost entirely of Parker's making) by Peter Guralnick, the most acclaimed music writer of his generation, it presents these two misunderstood icons as they've never been seen before: with all of their brilliance, humor, and flaws on full display."--Amazon.